2007
DOI: 10.1093/heapol/czm026
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in delays in diagnosis and treatment of tuberculosis

Abstract: Compared with men, women experienced longer delays at various stages of the clinical process of help seeking for TB. This warrants appropriate measures to improve the situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
61
4
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 6 publications
13
61
4
11
Order By: Relevance
“…Similar reasons were described in another study: patients "thought symptoms would go away" and "symptoms not considered serious" 13 . It has also been reported that patients awaiting symptoms resolution without specific treatment and can assign them to viral infections 26,27,28,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar reasons were described in another study: patients "thought symptoms would go away" and "symptoms not considered serious" 13 . It has also been reported that patients awaiting symptoms resolution without specific treatment and can assign them to viral infections 26,27,28,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…6 Karim et al mentioned that female TB patients experienced signifi cantly longer delays than males in health care seeking, diagnosis and initiation of DOTS-based treatment. 6 Many other studies conducted in different settings also found that delays at every stage of health care seeking and the clinical process of TB control were signifi cantly longer in females than in males. 12,21-23 However, we did not fi nd any signifi cant associations between sex and treatment delay in our study.…”
Section: Other Findingsmentioning
confidence: 99%
“…6,7 Delays in diagnosis and treatment initiation may aggravate disease conditions and clinical outcomes, and enhance transmission of TB in the community. 8,9 This is a major public health problem in densely populated countries such as Bangladesh.…”
mentioning
confidence: 99%
“…In a large variety of conditions, such as coronary artery disease [8,11,18], Parkinson's disease [9], irritable bowel syndrome [19], neck pain [20], knee joint arthrosis [21] and tuberculosis [10], men are investigated and treated more extensively than women with the same severity of symptoms. In a recent study of treatment in psoriasis, the number of patients and the severity of the disease did not differ between men and women, yet there was far more expenditures for clinic-based treatment for male patients, than female patients who received emollients for self-care to a greater extent [22].…”
Section: Gender Bias In Clinical Practicementioning
confidence: 99%
“…There is also evidence that women, for no apparent medical reason, are not offered the same treatment as men, a phenomenon that raises the question of gender bias. Many studies, for example, show that women are less likely than men to receive more advanced diagnostic and therapeutic interventions [6][7][8][9][10][11].…”
mentioning
confidence: 99%